The role of 1-Aminocyclopropane-1-Carboxylate Deaminase (ACCD) in plant-microbe interaction and Iycopene content of tomato. - Ahmad Ghazali, Amir Hamzah (Universiti Sains Malaysia, 2015)
Plants require an optimal level of ethylene (phytohormones) for normal growth and function, any increase in ethylene may cause deleterious effects. However, certain plant growth promoting rhizobacteria (PGPR) were able to produce 1- aminocyclopropane-1-carboxylate deaminase enzyme (ACC deaminase), a cleaving enzyme that optimized the deleterious level of ethylene and promoted normal plant growth. In the present study, our main focus will be on the cumulative effects of ACC deaminasee of locally isolated Burkholderia sp. USM B20 and E. coli USM L2, Azospirillum brasilense (Sp7) and Herbaspirillum seropedicae (Z 78) on ethylene levels and plant growth promotion of host plants. Earlier results have shown the ability of A. brasilense Sp7 and locally isolated Burkholderia sp. USMB 20 to produce ACC deaminase and optimize the endogenous ethylene levels and enhanced nodule formation of Mucuna bracteata. Our results also showed highly significant (pSO.01) interaction of A. brasilense Sp7, H. seropedicae Z 78 and inoculation frequency in promoting growth